EVALUATION OF THE INDEPENDENT CURRICULUM IMPLEMENTATION PROGRAM IN PAI LEARNING : Evaluasi Program Implementasi Kurikulum Merdeka pada Pembelajaran PAI di SD Negeri 2 Tual - St Jumaeda; Rahmat Abidin, Andi; Nirmala, Nirmala; Nure khun rikhte husaini; Saddam Husein (IAIN Ambon, 2024)
The aim of this research is to evaluate the implementation of the independent curriculum in Islamic Religious Education learning at SD Negeri 2 Tual looking at the context, input, process and product aspects. This type of research is evaluation research developed by Stuffelebeam, which includes four main components, namely: (context, input, process and product) with a qualitative approach. The research subjects consisted of school principals, PAI teachers and students. Data collection techniques use observation, interviews and documentation. The results of the research show that the implementation of the independent curriculum in Islamic Religious Education learning at SD Negeri 2 Tual has overall gone well. At the context stage, the independent curriculum has been prepared taking into account the needs and characteristics of students. In terms of input, the school has prepared adequate facilities and infrastructure as well as competent teacher and education staff resources in implementing the independent curriculum. In the process stage, the implementation of PAI learning uses varied and student-centered methods. At the product stage, student learning outcomes in PAI subjects showed a significant increase after the implementation of the independent curriculum. However, there are still several aspects that need to be optimized, such as socializing the independent curriculum to parents of students and increasing teacher competence in designing innovative learning and active participation of students in learning are still aspects that can be improved.